PHOTO EFFECT EVENT PHOTONS AND THEIR CHARACTERISTICS - Kakhkharov Siddiq Kakhkharovich; Makhmudov Furqat Djumaboyevich (International Engineering Journal For Research & Development, 2021)
This article discusses the advantages of using interactive methods in quantum physics topics.